PERINATAL TUBERCULOSIS WITH MILLIARY PATTERN IN INFANT AGED 28 DAYS - Savitri, Dian; Purniti, Putu Siadi; Kardana, Made (Medicina; Vol 45 No 3 (2014): September 2014)
Perinatal  tuberculosis  (TB) was a very  rare  case.  Its  clinical manifestations  could mimic bacterialinfection. The clinical course was often fulminant and characterized by dissemination and meningitis.Its mortality was very high, could achieve 100% in untreated patient. We reported a case of infant aged28  days  admitted with  breathlessness,  fever,  and  poor  feeding.  Physical  examination  showedbreathlessness, pale, lethargy, and hepatomegaly. Chest radiograph showed a feature of milliary patternwith fine tubercles in both lung, supported with positive result on gastric aspirates for acid fast bacilli3 days respectively. Gastric aspirate culture for Mycobacterium tuberculosis showed positive result.Patient then diagnosed with perinatal TB with milliary pattern. This condition was accompanied withsevere sepsis and meningitis. Four TB regimens (isoniazid, rifampisin, pirazinamide, and ethambutol),corticosteroid, antibiotics were given. The patient was eventually died after receiving TB therapy for 13days. [MEDICINA 2014;45:208-212].
Keywords: tuberculosis, milliary, perinatal